Detection of antibodies to denatured human leucocyte antigen molecules by single antigen Luminex. (15th November 2020) - Gutiérrez‐Larrañaga, María; Riesco, Laura; Guiral, Sandra; Irure, Juan; Rodrigo, Emilio; Ocejo‐Vinyals, Javier; Martorell, Jaume; Caro, Jose L.; López‐Hoyos, Marcos; San Segundo, David
Abstract : The anti‐HLA antibody detection has been improved in sensitivity and specificity with solid‐phase antigen bead (SAB) assays based on Luminex. However, false positive results due to denatured HLA (dHLA) may arise after single antigen test. The aim of this study was to compare the performance of the two Luminex technology‐based anti‐HLA detection kits available in the market in showing undesired anti‐HLA antibody results. A prospective cohort was assessed for anti‐HLA antibodies with single antigen A manufacturer (AM) kit and a comparison cohort with single antigen B manufacturer (BM) kit. A total of 11 out of 90 patients in a prospective cohort presented monospecific HLA‐I antibodies with AM, and 5 out of 11 confirmed monospecific reaction with BM. Despite the confirmation of monospecific reaction with both manufacturers, 80% were assigned as dHLA reaction by specific crossmatch. Further comparative cohorts detected four out of six monospecific reactions with BM that were confirmed as possible dHLA reactions. A positive SAB test should rule out a reaction against a dHLA molecule, thus avoidance of prolonged waitlist periods or misattribution of anti‐HLA reactions after transplantation.